FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU SAFETY RIDING AWARENESS PADA PENGEMUDI OJEK ONLINE MAXIM DI KOTA KENDARI TAHUN 2023 - Ridha Farida Tasya; Irma Irma; Akifah Akifah (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2023)
Safety riding awareness is one way to minimuze the risk of traffic accidents. Safety Riding is a series of safe driving behaviors in preventing traffic accidents, related to safe driving procedures, complete facilities needed when driving, and vehicle conditions that can be used. The aims of this research was to determine the factors associated with safety riding awareness behavior in Maxim online motorcycle taxi drivers in Kendari City in 2023. The method that used is quantitative research with a cross sectional study design using chi-square and fisher's exact tests. The population in this study were Maxim online motorcycle taxi drivers in Kendari City with a sample of 100 drivers determined by accidental sampling technique. The results showed that there was a relationship between knowledge (p-value=0.000), completeness of PPE (p-value=0.000), participation in safety riding training (p-value=0.036) and vehicle condition (p-value=0.000). The conclusion obtained from the study is that there is a relationship between knowledge, completeness of Personal Protective Equipment (PPE), participation in safety riding training and vehicle conditions with safety riding awareness behavior in Maxim online motorcycle taxi drivers in Kendari City in 2023. It is expected that the company can provide socialization and training on safety riding that must be attended by all online motorcycle taxi drivers regularly such as 1x a month.